Jejunal intramural hematoma: Masquerading as a mass lesion - Namasivayam Selvarajan; Ramesh Singaravelu; Muralinath Sankaranarayana Reddy; Gopinathan Kathirvelu; Ashitha K Unny; Vidhya Tamizhvanan (Wolters Kluwer Medknow Publications, 2022)
Jejunal intramural hematoma (JIH) is rare. A 5-year-old girl, a known attention-deficit hyperactivity disorder child with paraneoplastic symptoms, on imaging showed a suspicion of Jejunal intramural mass with internal bleeding. Laparotomy showed a JIH. Evacuation of hematoma and Histopathological Examination (HPE) ruled out tumor. Possible explanation of the manifestation is suggested.